El régimen microempresas y su incidencia en el flujo de efectivo de la distribuidora Steeven de Machala, periodo 2021. - Saraguro Borbor, Priscilla Lisseth; Comina Pacheco, Josselyn Andrea (Universidad Técnica de Machala, 2022)
The tax impositions by the Internal Revenue Service (SRI), constitute an efficient mechanism in the collection of funds to cover the needs of the country, being the Tax Regime for Micro-enterprises (Resolution N° NAC-DEGRCGC20-00000011, published in the segment of the Official Gazette N° 148 of February 21, 2020), the tax with the highest collection generated during the years 2020 and 2021. The cadastre published in the official page of the IRS, stratifies under this regime all taxpayers whose commercial condition corresponds to the entrepreneurial and micro-entrepreneurial sector, as established in the "Organic Code of Production, Commerce and Investments and the corresponding Regulations, except those who are subject to the simplified tax regime" (p. 19). This tax corresponded to the payment of 2% on the total sales corresponding to the year 2020, a tax that was maintained until the year 2021, causing a mismatch on the cash flow of those taxpayers registered under this new regime. The problem to be investigated lies in the impact generated by the imposition of the Micro-enterprise Regime on the owner of Distribuidora Steeven due to the lack of knowledge he had about it and about the percentage that he had to cancel on his sales during the year 2021, amount that was not foreseen in his work budget; due to his commercial activity, and especially to the initial economic reactivation due to the COVID-19 pandemic, he did not have enough liquidity to cover his tax obligations. Another factor is the requirement of compliance with a range of purchases by its main suppliers and the bank indebtedness obtained to reactivate its activities; in this way, a gap is generated in its finances, implying a decrease in its profits. Distribuidora Steeven located in the city of Machala, has as its business activity the sale of products for mass consumption, during the year 2021, has incurred in a low level of profitability due to tax compliance required by current legal regulations to be registered under the microenterprise regime in the database of the Internal Revenue Service (SRI), which implies that its obligations on the payment of 2% was inevitable due to the high values it had to cancel for compliance; Likewise, in view of the demands of its main suppliers for imposing high monthly purchase amounts, it incurred in the indebtedness of private banks to comply with its payments; with the above, in consideration of the high volume of purchases, its sales on direct credit had an impact on a weak portfolio recovery, rising simultaneously during the first and second semester of 2021. The object of the research is focused on the impact generated by the Microenterprise Tax Regime and its incidence on the cash flow; from this point of view, the following questions are posed: What are the tax obligations imposed under the Microenterprise Regime; Does Distribuidora Steeven have enough cash flow to meet its tax obligations; What is the impact generated on tax compliance and cash flow; questions that are posed under the guideline of the variables involved in the problem evidenced; and What is the impact generated on tax compliance and cash flow, questions that are posed under the guideline of the variables involved in the problem evidenced. The objective of this research work is to determine the impact generated from the Microenterprise Regime in the Distribuidora Steeven of the city of Machala through the analysis of the cash flow in the period 2021; for this purpose, the methodology applied is non-experimental, under the inductive method, descriptive in scope, with a transversal axis considering the time and space where it is developed; In addition, with the interpretative paradigm, a general analysis of the problem evidenced is carried out; likewise, through the application of a documentary observation guide and an interview with the business owner, the main causes of the problem under study are determined. The main results show that Distribuidora Steeven makes a high payment of 2% on sales as it is categorized under the Microenterprise Regime; it also maintains a high indebtedness with private banks to cover amounts demanded by its suppliers; finally, it denotes a low liquidity in its cash flow due to weak recovery of overdue accounts receivable from customers
Las imposiciones tributarias por parte del Servicio de Rentas Internas (SRI), constituyen un mecanismo eficiente en la recaudación de fondos para cubrir las necesidades del país, siendo el Régimen Impositivo para Microempresas (Resolución N° NAC-DEGRCGC20-00000011, publicada en el segmento del Registro Oficial N° 148 del 21 de febrero 2020), el impuesto con mayor recaudación generada durante los años 2020 y 2021. El catastro publicado en la página oficial del SRI, estratifica bajo este régimen a todos los contribuyentes cuya condición comercial corresponde al sector emprendedor y microempresarial, según lo establece el “Código Orgánico de la Producción, Comercio e Inversiones y el Reglamento correspondiente, salvo aquellos que se encuentren sujetos al régimen impositivo simplificado” (p. 19). Impuesto que correspondió al pago del 2% sobre sobre el total de ventas correspondiente al año 2020, impuesto que se mantuvo hasta el año 2021, ocasionando un desajuste sobre el flujo de efectivo en aquellos contribuyentes catastrados bajo este nuevo régimen. El problema a investigar radica en el impacto que generó la imposición del Régimen de Microempresas al propietario de la Distribuidora Steeven debido al desconocimiento que tenía sobre el mismo y sobre todo porcentaje que tuvo que cancelar sobre sus ventas durante el año 2021, monto que no estaba previsto en su presupuesto de trabajo; debido a su actividad comercial, y sobre todo a la inicial reactivación económica por la pandemia de COVID-19, no contaba con suficiente liquidez para cubrir sus obligaciones tributarias.; otro factor que incide, es la exigencia de cumplimiento de un rango de compras por parte de sus principales proveedores y el endeudamiento bancario obtenido para reactivar sus actividades; de esta manera, se genera un desfase en sus finanzas, implicando una disminución de sus utilidades. Distribuidora Steeven ubicada en la ciudad de Machala, tiene como actividad comercial la venta de productos para consumo masivo, durante el año 2021, ha incurrido en un bajo nivel de rentabilidad debido al cumplimiento tributario que exige la normativa legal vigente al ser catastrada bajo el régimen microempresas en la base de datos del Servicio de Rentas Internas (SRI), lo que implica que sus obligaciones sobre el pago del 2% fue inevitable debido a los altos valores que tuvo que cancelar para su cumplimiento; así mismo, ante la exigencia de sus principales proveedores por imponer elevados montos de compras mensuales, incurrió al endeudamiento de la banca privada para cumplir con sus pagos; con lo que antecede, en consideración al alto volumen de compras, sus ventas a crédito directo incidieron en una débil recuperación de cartera, elevándose simultáneamente durante el primer y segundo semestre del 2021. El objeto que persigue la investigación se direcciona en el impacto que generó el Régimen Impositivo de Microempresas y su incidencia sobre el flujo de efectivo; desde este punto de vista, se plantean las siguientes preguntas: ¿Cuáles son las obligaciones tributarias impuestas bajo el Régimen Microempresas?; ¿Cuenta Distribuidora Steeven con suficiente flujo de efectivo para cumplir con sus obligaciones tributarias?; ¿Cuál es el impacto generado sobre el cumplimiento tributario y flujo de efectivo?, interrogantes que son planteadas bajo directriz de las variables intervinientes en el problema evidenciado. El presente trabajo investigativo tiene como objetivo determinar el impacto generado a partir del Régimen de Microempresas en la Distribuidora Steeven de la ciudad de Machala mediante el análisis del flujo de efectivo en el periodo 2021; para el efecto, la metodología aplicada es no experimental, bajo el método inductivo, de alcance descriptivo, con eje transversal considerando el tiempo y espacio donde se desarrolla; además, con el paradigma interpretativo se realiza un análisis general del problema evidenciado; así mismo, mediante la aplicación de una guía de observación documental y entrevista al propietario del negocio se determinan las causas principales del problema objeto de estudio. Los principales resultados, denotan que en la Distribuidora Steeven realiza un pago elevado del 2% sobre ventas al ser categorizado bajo el Régimen Microempresas; además, mantiene un endeudamiento elevado con la banca privada para cubrir montos exigidos por sus proveedores; finalmente, denota una baja liquidez en su flujo de efectivo por débil recuperación de cartera vencida con clientes.
Keywords: CATASTRO; CUMPLIMIENTO TRIBUTARIO; FLUJO DE EFECTIVO; IMPUESTOS